2017
DOI: 10.1016/j.jhep.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma stem-like subset shapes tumor-initiating niche by educating associated macrophages

Abstract: Background & Aims A therapeutically challenging subset of cells, termed cancer stem cells (CSCs) are responsible for cholangiocarcinoma (CCA) clinical severity. Presence of tumor-associated macrophages (TAMs) has prognostic significance in CCA and other malignancies. Thus, we hypothesized that CSCs may actively shape their tumor-supportive immune niche. Methods CCA cells were cultured in 3D conditions to generate spheres. CCA sphere analysis of in vivo tumorigenic-engraftment in immune-deficient mice and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 48 publications
5
119
0
Order By: Relevance
“…In CCA tissue, TAMs are predominantly localized at the tumor front 37 , and their number was shown to positively correlate with the presence of extrahepatic metastases 38 . Furthermore, incubation of CCA cells with conditioned medium from M2 macrophages increased cancer cell migration, while promoting EMT-like changes 38 .…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
“…In CCA tissue, TAMs are predominantly localized at the tumor front 37 , and their number was shown to positively correlate with the presence of extrahepatic metastases 38 . Furthermore, incubation of CCA cells with conditioned medium from M2 macrophages increased cancer cell migration, while promoting EMT-like changes 38 .…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
“…They found that, in CCA tissues, the number of CD163 + M2 cells was, as expected, lower than the number of CD68 + cells, and that high infiltration of M2 macrophages, but not of total macrophages, was significantly associated with poor disease-free survival of patients. Of further interest, the density of M2 macrophages within CCA stroma also correlated with the presence of extrahepatic metastases[28], the tumor pathological grade[67], and the microvascular density[64]. Although these findings are based on the evaluation of different phenotypic markers, overall, they suggest that TAMs strongly influence CCA progression, with a major role played by M2 TAMs, thus confirming what observed in other cancer types.…”
Section: Tumor-associated Macrophagesmentioning
confidence: 62%
“…In CCA tissues, M2 macrophages are definitely much more abundant than in the peritumoral areas, and TAM are mostly located at the leading edge of the tumor[67]. Consistently, immunohistochemical analyses in Opisthorchis viverrini -associated CCA in a hamster model revealed a progressive, dramatic increase in M2 macrophages through carcinogenesis[28].…”
Section: Tumor-associated Macrophagesmentioning
confidence: 87%
See 2 more Smart Citations